ANALYSIS OF THE USE OF TRAVELOKA PLATFORM IN BOOKING AIRLINE TICKETS FOR USERS IN BATAM CITY - Septianti, Khainur Nisa; Sihombing, Dame Afrina; Hariyanto, Oda Ignatius Besar (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examines the relationship between the role of online reviews usefulness and credibility in driving customer satisfaction and continued use of Traveloka. Set within the context of Indonesia’s post-pandemic tourism recovery and the growing competition in the digital marketplace, the research underscores the importance of understanding consumer behaviour in the tourism sector. Adopting a quantitative approach, data were collected from 300 respondents in Batam City, Riau Islands Province, using purposive sampling through an online survey. Data analysis was conducted using structural equation modelling with partial least squares. The results reveal that consumer reviews significantly influence customer satisfaction by offering reliable information regarding service quality and convenience. Positive reviews help people trust the platform, which makes them more likely to keep using it. In addition, the findings show that customer satisfaction has a significant positive impact on the intention to continue using the service, meaning that satisfied users are more likely to maintain their engagement and consistently use the Traveloka digital platform over time. However, external factors, such as government policies and macroeconomic changes, may also impact travellers' preferences. To enhance the competitiveness of digital platforms in the travel industry, the study highlights the critical role of continuous innovation. Keywords: Online Travel Agent (OTA); Customer Satisfaction; Consumer Online Reviews; Customer Satisfaction; Continuance Intention